2018
DOI: 10.20535/2523-4455.2018.23.1.126231
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of nickel nanoparticles in systems with a statistically inhomogeneous structure

Abstract: The analysis and further development of the experimental-analytical approach for determining the values of the optical parameters of nanosized particles for a system with a statistically inhomogeneous structure is presented. An improved experimental-analytical method for determining the complex specific electric polarizability of nanosized particles in systems with a statistically inhomogeneous structure is based on spectrophotometric and electron-microscopic measurements on two-dimensional structures and appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
(20 reference statements)
1
5
0
1
Order By: Relevance
“…In the continuation of the investigations of the optical properties of nanoparticles in statistical inhomogeneous systems that we started in [24,27] with the help of an experimental analytical method, the optical characteristics of nanosized copper particles in a two-dimensional system islet copper film on a quartz substrate are determined. It is shown that taking into account the analysis of the particle size distribution in the experimental-analytical method makes it possible to apply this approach to nanostructured systems with a statistically inhomogeneous structure and reliably estimate their optical parameters.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the continuation of the investigations of the optical properties of nanoparticles in statistical inhomogeneous systems that we started in [24,27] with the help of an experimental analytical method, the optical characteristics of nanosized copper particles in a two-dimensional system islet copper film on a quartz substrate are determined. It is shown that taking into account the analysis of the particle size distribution in the experimental-analytical method makes it possible to apply this approach to nanostructured systems with a statistically inhomogeneous structure and reliably estimate their optical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The values of copper nanoparticle complex specific electric polarizability are determined by experimentalanalytical method, taking into account the analysis of the particle distribution by size statistics [24]. The method is based on experimental studies of microstructure and spectrophotometric measurements of reflection transmission coefficients on two-dimensional systems and analytical solution of the inverse problem of the spectrophotometric system of Rosenberg equations, taking into account the function of nanoparticles distribution by size.…”
Section: Methodology and Materials Of The Experi-mentmentioning
confidence: 99%
See 3 more Smart Citations